The development and initial validation of the Earthquake Fear Scale: Its links to personality traits, psychological distress, harmony in life, and mental wellbeing - Satici, Seydi Ahmet; Okur, Sinan; Deniz, M. Engin; Karaagac, Zahide Gul; Yilmaz, Fatma Betuel; Kutuk, Hasan; Satici, Begum; Kaya, Yagmur (WILEY, 2024)
Unexpected and unpredictable earthquakes may have a negative impact on people's mental health. The earthquake fear experienced by individuals causes psychological problems. This article is made up of three different studies that look at earthquake fear. The seven item Earthquake Fear Scale (EFS) was confirmed in Study I (N = 407) utilising confirmatory factor analysis. In addition, Item Response Analysis was done, and it was found that all of the items showed a good degree of discrimination. The reliability of the EFS has been proven with different reliability coefficients. In Study II (N = 505), both correlation and network analysis were carried out, and earthquake fear was found to be significantly associated with depression, anxiety, stress, and mental wellbeing. Moreover, neuroticism and conscientiousness, two of the big five personality traits, are significantly associated with earthquake fear. In Study III (N = 382), it was revealed that psychological distress and harmony in life play a serial and fully mediating role in the link between earthquake fear and mental wellbeing. The psychological influence of earthquake fear is emphasised in this pioneering and comprehensive study on earthquake fear.
Keywords: earthquake fear; harmony in life; mental wellbeing; personality traits; psychological distress; POSTTRAUMATIC-STRESS-DISORDER; ITEM RESPONSE THEORY; DEPRESSION; PREVALENCE; SURVIVORS; ANXIETY; VERSION; RISK; PREDICTORS; PERCEPTION; Psychology; Psychiatry